2016
DOI: 10.1145/2818990
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal biometrics for enhanced mobile device security

Abstract: Fusing information from multiple biometric traits enhances authentication in mobile devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…An EER of 0.1% has been obtained for use in a quiet office, and an EER of 0.3-0.6% for use in a noisy cafeteria. The authors of [27] have shown the potential of multimodal biometrics for protecting consumer mobile devices from unauthorized access. They have implemented Proteus based on face and voice biometrics.…”
Section: Related Workmentioning
confidence: 99%
“…An EER of 0.1% has been obtained for use in a quiet office, and an EER of 0.3-0.6% for use in a noisy cafeteria. The authors of [27] have shown the potential of multimodal biometrics for protecting consumer mobile devices from unauthorized access. They have implemented Proteus based on face and voice biometrics.…”
Section: Related Workmentioning
confidence: 99%
“…Because almost all mobile devices integrate biometric sensors such as cameras, microphones or fingerprint scanners, the next natural step is to fuse their information using multimodal biometrics, which can provide higher accuracy and increase the difficulty of spoofing attacks [19].…”
Section: Personal Devicesmentioning
confidence: 99%
“…Together with the advances in embeddable high-quality sensors, those trends have sparked interest in (single and multi modal) mobile biometrics, which has become an active area of research and product development (see e.g. [16], [17], [18], [19], [20]).…”
Section: Introductionmentioning
confidence: 99%